Grondslagen van verandering. Assimilatie en differentiatie van het Antwerpse boekbedrijf in de tweede helft van de zeventiende eeuw - Verhoeven, Gerrit (BMGN - Low Countries Historical Review, 2007)
The foundations of change. Integration and diversification in the Antwerp book trade during the second half of the seventeenth centuryWar, ruthless international competition, high import and export duties on books, and unforeseeable changes in the taste of readers all posed a serious threat to the survival of the book trade in the Southern Netherlands during the late seventeenth century. Nevertheless, some Brabantine printers not only survived the crisis they even managed to prosper. This article provides additional insights into the survival strategies adopted at the time based on material from the archives of Balthazar II Moretus’ Officina Plantiniana and the medium-sized publishing house of Hieronymus III Verdussen. Although both entrepreneurs reacted to the crisis by imposing harsh reforms, restructuring, and implementing innovative techniques such as sale on approval, their actual management choices differed greatly. The Officina Plantiniana focused more on the industrial component by opting for large-scale printing. Moretus cut back deliveries to smaller markets and dealers and concentrated on the major booksellers instead as they were able to order in bulk and resell the books to their smaller colleagues which meant that he no longer had to pay for transport and marketing. Moretus also abandoned the inefficient barter system and insisted upon cash payments so that he no longer had to take on books with a limited market value. Verdussen on the other hand followed a completely different path and seemed to renounce printing. He outsourced more and more printing work to jobbing printers in Germany or the United Provinces, thereby externalizing the risk of overstocking or losing out due to a drop in demand. By cultivating a number of advantageous alliances, Verdussen was also able to drastically reduce his custom and transport costs. As the registers of their guild reveals, in order to survive the crisis the majority of publishers in Antwerp chose Verdussen’s course of commercial capitalism as opposed to the industrial approach followed by Moretus.